EFEKTIVITAS PENERAPAN POLA ASUH SEHAT MENTAL TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK PRASEKOLAH USIA 3-6 TAHUN - Susana Nurtanti; Nita Yunianti R (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The background of this research is the increasing number of child abuse committed by parents and those nearest that hinder the psychosocial development. The purpose of this study was to analyze the effectiveness of mental health parenting to the psychosocial development of pre-school age children 3-6 years in TK Pertiwi I Pracimantoro. This study uses a study design one group pre post test design. The samples were all parents in TK Pertiwi I who have children aged three to six years some 23 peoples. The dependent variable in this study is mental health parenting, the independent variable is the psychosocial development of preschool children 3-6 years. The research instrument used was a questionnaire. Data analysis using SPSS version 17 for analyzing the characteristics of respondents by age, gender, occupation and number of children, to analyze the effect of mental health parenting to psychosocial development of children aged 3-6 years with T test. The results show the value of t is greater than t table so that there is a significant effect. p-value 0.000 > 0.05 (95% confidence level) showed differences in the psychosocial development before and after the application of mental health parenting. The mean result is 18 174 before treatment, after treatment is 20 478 there is a difference score of 2.304 indicating an increase in psychosocial development of preschool children 3 – 6 years after getting treatment of mental health parenting of parents.Keywords: Mental Health Parenting, Psychosocial Development, Preschool children age 3-6 years.